Adoption of Mobile Wallets in Nepal: Examining the Influence of Trust and the Mediating Role of Security and Privacy (The International Research Journal of Management Science, 2024)
Purpose: This study investigates the impact of trust on the intention of using mobile financial services, focusing on mobile payment platforms. It also explores how security andprivacy mediates this relationship.Methodology: A quantitative research approach was employed, utilizing a structured questionnaire to collect data from 384 respondents. The data were analyzed using Structural Equation Modeling (SEM) to test the hypothesized relationships between trust, security, privacy, and the intentionto use the mobile payment platform.Findings: The results indicate that trust significantly influences users' intention to adopt the mobile payment platform whereas security and privacy concerns play crucial mediating roles. TheSEM analysis confirmed that the model fit indices were within acceptable ranges, supporting the robustness of the proposed model.Implications: For service providers, enhancing security and privacy features is essential for fostering trust and encouraging user adoption of mobile financial services, and it can be a key driver in the growth of digital finance.Originality/Value: The study contributes to the literature on digital finance by highlighting the intertwined roles of trust, security, and privacy in shaping consumer behavior, offering insights for both academia and industry practitioners.